2021
DOI: 10.1186/s12933-021-01263-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with direct oral anticoagulants or warfarin and the risk for incident diabetes among patients with atrial fibrillation: a population‐based cohort study

Abstract: Background Diabetes mellitus is a common comorbidity of atrial fibrillation (AF), which can complicate the management of AF. The pharmacology of oral anticoagulants (OACs) have been implicated in pathogenesis of diabetes, but the relationship between different OACs and risk of diabetes remains unexamined. This study aimed to evaluate the risk of diabetes with use of different OACs in AF patients. Methods Population-based retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Our study was based on two cohort studies with a total sample size of 24,434, which is the most comprehensive and latest study according to the risk of DOACs vs. warfarin in inducing new-onset diabetes in AF patients. The result in the cohort study from Cheung et al ( 15 ) proposed that only dabigatran was significantly associated with incident diabetes risk reduction, our results support that three of existing approved DOAC dabigatran, apixaban, and rivaroxaban with the function of reducing incident diabetic risk. At the same time, this effect in factor Xa inhibitors rivaroxaban and apixaban were not obvious, and our findings confirmed that all of these three drugs with the risk reduction ability.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our study was based on two cohort studies with a total sample size of 24,434, which is the most comprehensive and latest study according to the risk of DOACs vs. warfarin in inducing new-onset diabetes in AF patients. The result in the cohort study from Cheung et al ( 15 ) proposed that only dabigatran was significantly associated with incident diabetes risk reduction, our results support that three of existing approved DOAC dabigatran, apixaban, and rivaroxaban with the function of reducing incident diabetic risk. At the same time, this effect in factor Xa inhibitors rivaroxaban and apixaban were not obvious, and our findings confirmed that all of these three drugs with the risk reduction ability.…”
Section: Discussionsupporting
confidence: 84%
“…Then 10 studies were evaluated in detail. On the basis of predefined criteria, finally, two eligible cohort studies were included in our meta-analysis ( 9 , 15 ). Exhibited in Table 1 was the baseline information of patients in the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disruption of this pathway causes the formation of fibrin threads that function to close wounds and capture blood cells to help blood clot. An increase in bleeding duration, prothrombin time (PT) and activated partial thromboplastin time (APTT) is one indication of the active mechanism of warfarin in the body (Cheung et al, 2021).…”
Section: Discussionmentioning
confidence: 99%